2013
DOI: 10.1038/ncomms3489
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic performance of the feathered dinosaur Microraptor and the evolution of feathered flight

Abstract: Understanding the aerodynamic performance of feathered, non-avialan dinosaurs is critical to reconstructing the evolution of bird flight. Here we show that the Early Cretaceous five-winged paravian Microraptor is most stable when gliding at high-lift coefficients (low lift/ drag ratios). Wind tunnel experiments and flight simulations show that sustaining a high-lift coefficient at the expense of high drag would have been the most efficient strategy for Microraptor when gliding from, and between, low elevations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 34 publications
7
90
1
1
Order By: Relevance
“…Furthermore, the presence of large feathers on the tail, forelimbs and hindlimbs in Jianianhualong confirms that these feathering characteristics were widely present in basal paravians54. This provides a robust troodontid basis for deepening understanding of the aerodynamic capabilities of this condition, beyond the gliding-related insights from the Jehol dromaeosaurid Microraptor 5556.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, the presence of large feathers on the tail, forelimbs and hindlimbs in Jianianhualong confirms that these feathering characteristics were widely present in basal paravians54. This provides a robust troodontid basis for deepening understanding of the aerodynamic capabilities of this condition, beyond the gliding-related insights from the Jehol dromaeosaurid Microraptor 5556.…”
Section: Discussionmentioning
confidence: 55%
“…[57] also found this posture to be stable. In contrast, Xu et al (as described on television in [34]), found the biplane to be unstable in wind tunnel tests except at high angle of attack.…”
Section: Discussionmentioning
confidence: 77%
“…Biomechanical study of the four-winged dromaeosaurid Microraptor suggests that it was a capable glider, although probably not capable of the kind of muscle-driven powered flight of living birds [61]. In further support of Microraptor's volant capabilities, it is the only taxon with asymmetrical hindlimb feathers (flight feathers are asymmetrical with a short and stiff leading vane and are optimized to withstand the force of the airstream), and the only non-avian with an elongated coracoid, a feature of all early birds in which a sternum is present (Jeholornis, Confuciusornis, and ornithothoracines) [62].…”
Section: The Assembly Of the Bird Body Plan And Classic Avian Behaviorsmentioning
confidence: 99%